2020
DOI: 10.21203/rs.3.rs-96892/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Traditional use of medicinal plants in the Chyangthapu-Phalaicha biological sub-corridor, Panchthar District, Kangchenjunga Landscape, Nepal

Abstract: Background: Chyangthapu-Phalaicha located in the northeastern Panchthar District, is a biodiversity hotspot in the Eastern Himalaya. The area is dominated by the Kirat indigenous community. The present study was conducted to document the knowledge of the ethnomedicinal uses and practices that exist in the area before the associated socio-cultural knowledge on biological diversity is lost. Methods: Ethnomedicinal data were collected through three focus group discussions and 47 key informant interviews using sem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…The medicinal values of varieties of Nepalese plants from different localities have been reported in previous studies (Rajbhandari & Lindequist, 2020;Joshi & Bashyal, 2018, Subba & Thapa, 2018. However, few works have been reported on the medicinal plants from the Panchthar district of Nepal (Bhandari et al, 2020;Gautam, 2011).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The medicinal values of varieties of Nepalese plants from different localities have been reported in previous studies (Rajbhandari & Lindequist, 2020;Joshi & Bashyal, 2018, Subba & Thapa, 2018. However, few works have been reported on the medicinal plants from the Panchthar district of Nepal (Bhandari et al, 2020;Gautam, 2011).…”
Section: Introductionmentioning
confidence: 83%
“…Panchthar district of Nepal is one of the most important natural storehouses of medicinal plants owing to its geographical diversity, variations in topography, altitude, climatic gradients, and biological resources of flora and fauna (Gautam, 2011). A recent review on the ethnomedicinal study of the Chyangthapu-Phalaicha biological sub-corridor of the northern part of Panchthar district located in the Kangchenjunga Landscape indicated that the area has significant medicinal plants and traditional knowledge associated with it (Bhandari et al, 2020). The use of the medicinal plants in the area indicates the need for their cultivation, processing and phytochemical investigation, especially for those with high ethnobotanical indices.…”
Section: Introductionmentioning
confidence: 99%